2014
DOI: 10.4238/2014.january.24.20
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of DNA repair-related genes with susceptibility and prognosis of prostate cancer

Abstract: ABSTRACT. We aimed to investigate the association between genetic variants of the DNA repair genes XPG, CSB, XPC, CCNH, and MMS19L in the nucleotide excision repair (NER) pathway and risk of prostate cancer in a population in China. This study included 229 patients with newly diagnosed and histopathologically confirmed primary prostate cancer and 238 healthy controls. Genotyping of XPG, CSB, XPC, CCNH, and MMS19L were performed on a 384-well plate on the MassARRAY platform. Associations between the polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Steck et al (2014) did not find significant association between XPG gene polymorphisms and colon cancer risk. Zhang et al (2014) reported that the XPG rs2296147 polymorphism was significantly correlated with prostate cancer susceptibility in a Chinese population. Zhu et al (2012) suggested that XPG rs2296147 C variant genotypes were associated with a significantly lower ESCC risk in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steck et al (2014) did not find significant association between XPG gene polymorphisms and colon cancer risk. Zhang et al (2014) reported that the XPG rs2296147 polymorphism was significantly correlated with prostate cancer susceptibility in a Chinese population. Zhu et al (2012) suggested that XPG rs2296147 C variant genotypes were associated with a significantly lower ESCC risk in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that XPG gene polymorphisms are associated with several kinds of cancers in different ethnicities, such as head and neck cancer, gastric cancer, bladder cancer, colon cancer, prostate cancer (Ma et al, 2012;He et al, 2012;Zhu et al, 2012;Liu et al, 2014;Steck et al, 2014;Zhang et al, 2014). Ma et al (2012) conducted a casecontrol study of 1059 patients with head and neck cancer and 1066 control subjects, and they reported that XPG gene polymorphisms may not affect the risk of head and neck cancer in an American population.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are vague conclusions about the relationship between XPC rs2228001 A/C polymorphism and PCa susceptibility in different case‐controlled studies. Hence, a systematic analysis based on all eligible studies was conducted to further investigate the correlation between the XPC rs2228001 A/C polymorphism and PCa risk 17‐28 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, low penetrance of those genes was demonstrated in prostate cancer [5][6][7]. Therefore, many studies have investigated the possible association between the mutations or polymorphisms in DNA repair genes and the development of prostatic carcinoma [8].…”
Section: Genetic Toxicology Introductionmentioning
confidence: 99%